THE EFFECT OF TRANSPARENCY AND ACCOUNTABILITY OF VILLAGE FUND FINANCIAL MANAGEMENT IN CREATING GOOD GOVERNANCE - Hariyanti, Tiwuk Puji; Rusiyanto, Rudi; Dewi, Retno Sari; Purwati, Erma (2021)
The purpose of this study was to determine the effect of village transparency and accountability in using Village Fund Allocations to build Good Governance. This study uses a qualitative-descriptive type of research. This research was conducted on Village Fund Allocation in Boyolangu sub-district, Tulungagung district. The types of data sources in the research are primary data sources and secondary data sources. Data collection techniques used in-depth interviews, documentation, and literature studies. To test the validity of the data obtained, this study uses two methods of triangulation techniques, namely data source triangulation and theoretical triangulation. Presentation of data using qualitative methods. Based on the results of data analysis and discussion, it can be concluded that: 1) The planning stage of Village Fund Allocation in 3 (village) villages has implemented the principles of participation and transparency; 2) The implementation phase of the Village Fund Allocation program in 3 (three) villages in Boyolangu District has implemented the principles of transparency and accountability; and 3) The accountability stage for Village Fund Allocation in 3 (three) villages in Boyolangu District has been directly accountable to the community. This happened because of transparency or openness by the village government as the manager of the Village Fund Allocation to the community in the form of information on the use of the Village Fund Allocation fund.